Induction help needed! :P

Using the principle of mathematical induction, prove that dnadxn=(1)nn!(x+5)n+1\frac{d^{n}a}{dx^{n}}=\frac{(-1)^{n}n!}{(x+5)^{n+1}} for a=1x+5a=\frac{1}{x+5}.

Just explain me the inductive step! Thanks :)

#Calculus #MathematicalInduction #Induction

Note by Omkar Kulkarni
6 years, 1 month ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

CASE I (n=1n=1): ddx1x+5=1(x+5)2=(1)11!(x+5)1+1\large \frac{d}{dx} \frac{1}{x+5} = \frac{-1}{(x+5)^2} = \frac{(-1)^{1} \cdot 1!}{(x+5)^{1+1}} \Rightarrow TRUE.

CASE II (n=kn=k): dkdxk1x+5=(1)kk!(x+5)k+1\large \frac{d^k}{dx^k} \frac{1}{x+5} = \frac{(-1)^k \cdot k!}{(x+5)^{k+1}} \Rightarrow ASSUMED TRUE.

CASE III (n=k+1n=k+1): ddx[dkdxk1x+5]=ddx[(1)kk!(x+5)k+1];\large \frac{d}{dx}[\frac{d^k}{dx^k} \frac{1}{x+5}] = \frac{d}{dx}[\frac{(-1)^k \cdot k!}{(x+5)^{k+1}}];

or dk+1dxk+11x+5=(1)k(k+1)k!(x+5)k+2;\large \frac{d^{k+1}}{dx^{k+1}} \frac{1}{x+5}= \frac{(-1)^k \cdot -(k+1) \cdot k!}{(x+5)^{k+2}};

or dk+1dxk+11x+5=(1)k+1(k+1)!(x+5)(k+1)+1\large \frac{d^{k+1}}{dx^{k+1}} \frac{1}{x+5} = \frac{(-1)^{k+1} \cdot (k+1)!}{(x+5)^{(k+1)+1}} \Rightarrow TRUE.

Q.E.D. \mathbb{Q.} \mathbb{E.} \mathbb{D.}

tom engelsman - 3 weeks, 3 days ago
×

Problem Loading...

Note Loading...

Set Loading...